Crosslinked polyolefin material and preparation method thereof

By using modified polyhedral oligosilsesquioxane and its derivative flame retardant synergist in crosslinked polyolefin materials, the problem of insufficient flame retardant performance of existing materials is solved, and efficient flame retardant and mechanical properties are achieved.

CN119752022APending Publication Date: 2025-04-04SHENZHEN WOER HEAT SHRINKABLE MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411993360.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The flame retardant properties of existing crosslinked polyolefin materials are insufficient, and it is difficult to meet the requirements of V0-level flame retardant properties and mechanical properties at the same time.

Method used

The formulation of a crosslinked polyolefin material is adopted, including ethylene-vinyl acetate copolymer or ethylene-acrylate copolymer, polyolefin elastomer, phosphorus-based flame retardant, nitrogen-based flame retardant, and modified polyhedral oligosilsesquioxane and its derivative flame retardant synergistic agent, and is extruded and granulated and dried by specific preparation methods.

Benefits of technology

It significantly improves the flame retardant properties and mechanical properties of the material, and can form a multi-layer protective structure during the combustion process, prevent dripping and effectively isolate heat and oxygen, achieving excellent flame retardant properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752022A_ABST
    Figure CN119752022A_ABST
Patent Text Reader

Abstract

The invention discloses a cross-linked polyolefin material which comprises an ethylene-vinyl acetate copolymer or an ethylene-acrylate copolymer, a polyolefin elastomer, a phosphorus flame retardant, a nitrogen flame retardant, modified polyhedral oligomeric silsesquioxane and a derivative flame retardant synergist thereof, a compatilizer and a cross-linking agent. The modified polyhedral oligomeric silsesquioxane and the derivative flame-retardant synergist thereof contain boron, an annular structure R2 with the carbon hydrogen ratio larger than 1 and two inorganic silicon cage cores, and the structures form a carbon layer, a ceramic barrier layer, a protective film or a heat-insulation coke layer and other protective layers in the combustion process, so that the anti-dripping effect is greatly improved, and meanwhile, the anti-dripping effect is greatly improved. Heat and oxygen transfer is isolated, combustible gas release is reduced, and the flame retardant property of the material is remarkably improved under the combined action of multiple mechanisms. Furthermore, the flame-retardant synergist of the modified polyhedral oligomeric silsesquioxane and the derivative of the modified polyhedral oligomeric silsesquioxane is matched with a phosphorus flame retardant for providing an acid source and a nitrogen flame retardant for providing a gas source to realize synergistic flame retardance, so that the flame retardance and the mechanical property of the cross-linked polyolefin material are improved while the dosage of the flame retardants is reduced. The cross-linked polyolefin material provided by the invention is excellent in flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a cross-linked polyolefin material. Background Art

[0002] Polyhedral oligomeric silsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.

[0003] Cross-linked polyolefin (XLPO) is a thermosetting material, which includes copolymers of various olefin monomers, among which ethylene-vinyl acetate copolymer (EVA), ethylene-acrylate copolymer, ethylene-octene copolymer (POE), and polyethylene (PE) are several common copolymers in XLPO. XLPO materials are widely used in shoe materials, pipes, injection molding and cable materials. Domestic halogen-free high flame retardant cable materials improve their flame retardancy by adding a large amount of aluminum hydroxide, magnesium hydroxide, aluminum hypophosphite, diethyl aluminum hypophosphite, melamine urate and other flame retardants, but these flame retardants need to be added in large amounts to pass the UL standard V0 flame retardant performance, which will cause the physical properties of the materials to decrease a lot and cannot meet the requirements of the mechanical properties of the products. There are also some cross-linked polyolefin materials that meet the V0 requirements on the market, but they are achieved by dripping the burning material, and the dripping material is extinguished during the falling process. This product has a great hidden danger. The development of cross-linked polyolefin materials that are drip-proof and can meet the V0 requirements is very necessary. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a cross-linked polyolefin material, aiming to solve the problem of poor flame retardancy of the current cross-linked polyolefin material.

[0005] The above object of the present invention is achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a cross-linked polyolefin material. The raw materials of the cross-linked polyolefin material, measured in parts by weight, include:

[0007] 35-55 parts of ethylene-vinyl acetate copolymer or ethylene-acrylate copolymer,

[0008] Polyolefin elastomer 10-15 parts,

[0009] Phosphorus flame retardant 10-20 parts,

[0010] 10-20 parts of nitrogen flame retardant,

[0011] 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,

[0012] 3-8 parts of compatibilizer,

[0013] Crosslinking agent 0.5-3 parts,

[0014] Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:

[0015]

[0016] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;

[0017] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

[0018] In some embodiments of the present invention, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group;

[0019] And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.

[0020] In some embodiments of the present invention, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

[0021]

[0022] In some embodiments of the present invention, the molar ratio of compound 1 to compound 2 is 2:1.

[0023] In some embodiments of the present invention, the method for preparing the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps:

[0024] Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist;

[0025] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;

[0026] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

[0027] In some embodiments of the present invention, the raw material of the cross-linked polyolefin material further comprises polyethylene, and the polyethylene accounts for 5-10 parts by weight.

[0028] In some embodiments of the present invention, the polyethylene includes at least one of low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, and metallocene polyethylene. ,

[0029] In some embodiments of the present invention, the ethylene-acrylate copolymer includes at least one of ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, and ethylene-methyl methacrylate copolymer;

[0030] And / or, the polyolefin elastomer comprises at least one of ethylene-butene copolymer and ethylene-octene copolymer;

[0031] And / or, the phosphorus-based flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate, phosphite, and phosphorus oxide;

[0032] And / or, the nitrogen-based flame retardant includes at least one of melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, and melamine.

[0033] In some embodiments of the present invention, the raw material of the cross-linked polyolefin material also includes at least one of a lubricant, an antioxidant, and a light stabilizer; wherein, the raw materials are calculated by weight: the lubricant is 0.2-1 part, the antioxidant is 0.5-2 parts, and the light stabilizer is 0.2-1 part.

[0034] In a second aspect of the present invention, there is provided a method for preparing the above cross-linked polyolefin material, comprising the following steps:

[0035] The raw materials, including ethylene-vinyl acetate copolymer or ethylene-butyl acrylate copolymer, polyolefin elastomer, phosphorus flame retardant, nitrogen flame retardant, modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, compatibilizer, and crosslinking agent, are mixed in an internal mixer according to weight parts to obtain an internal mixer material;

[0036] The mixed material is extruded and granulated through an extruder, and dried to obtain a granular material, namely the cross-linked polyolefin material.

[0037] In some embodiments of the present invention, the raw material further comprises at least one of a lubricant, an antioxidant, and a light stabilizer;

[0038] And / or, the extruder is a twin-screw extruder, the aspect ratio of the twin-screw extruder is (35-40):1, and the extrusion temperature is 110°C-150°C;

[0039] And / or, the drying temperature is 80°C-90°C.

[0040] The cross-linked polyolefin material of the present invention comprises ethylene-vinyl acetate copolymer or ethylene-acrylate copolymer, polyolefin elastomer, phosphorus flame retardant, nitrogen flame retardant, modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, compatibilizer and cross-linking agent. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives cooperates with the phosphorus flame retardant providing the acid source and the nitrogen flame retardant providing the gas source to synergize and flame retardant, thereby reducing the amount of the flame retardant and improving the flame retardant and mechanical properties of the cross-linked polyolefin material. The cross-linked polyolefin material provided by the present invention has excellent flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The molecular structure diagram of the modified POSS flame retardant synergist 1 of the present invention;

[0042] Figure 2 This is a molecular structure diagram of the modified POSS flame retardant synergist 2 of the present invention. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0044] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.

[0045] Polyhedral oligomeric silsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.

[0046] Cross-linked polyolefin (XLPO) is a thermosetting material, which includes copolymers of various olefin monomers, among which ethylene-vinyl acetate copolymer (EVA), ethylene-acrylate copolymer, ethylene-octene copolymer (POE), and polyethylene (PE) are several common copolymers in XLPO. XLPO materials are widely used in shoe materials, pipes, injection molding and cable materials. Domestic halogen-free high flame retardant cable materials improve their flame retardancy by adding a large amount of flame retardants such as aluminum hydroxide, magnesium hydroxide, aluminum hypophosphite, diethyl aluminum hypophosphite, and melamine urate (MCA). However, these flame retardants need to be added in large amounts to pass the UL standard V0 flame retardant performance, which will cause the physical properties of the materials to decrease a lot and cannot meet the mechanical properties requirements of the products. There are also some cross-linked polyolefin materials that meet the V0 requirements on the market, but they are achieved by dripping the burning material, and the dripping material is extinguished during the falling process. This product has a great hidden danger. The development of cross-linked polyolefin materials that are drip-proof and can meet the V0 requirements is very necessary.

[0047] In order to solve the above problems, the first aspect of the present invention provides a cross-linked polyolefin material. The raw materials of the cross-linked polyolefin material, measured in parts by weight, include:

[0048] 35-55 parts of ethylene-vinyl acetate copolymer or ethylene-acrylate copolymer,

[0049] Polyolefin elastomer 10-15 parts,

[0050] Phosphorus flame retardant 10-20 parts,

[0051] 10-20 parts of nitrogen flame retardant,

[0052] 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,

[0053] 3-8 parts of compatibilizer,

[0054] Crosslinking agent 0.5-3 parts,

[0055] Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:

[0056]

[0057] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;

[0058] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

[0059] It is understood that ethylene-acrylate copolymers are copolymerized by ethylene and acrylate, and mainly include ethylene-methyl acrylate copolymer (EMA), ethylene-ethyl acrylate copolymer (EEA), ethylene-butyl acrylate copolymer (EBA), and ethylene-methyl methacrylate copolymer (EMMA). The properties of ethylene-acrylate copolymers are related to the content, average molecular weight, molecular weight distribution, and long and short chain branches of acrylate monomers.

[0060] As can be understood, polyolefin elastomers (POE for short) are a type of thermoplastic elastomer formed by copolymerization of polyolefins (mainly polyethylene and polypropylene) and α-olefins (such as 1-butene, 1-hexene or 1-octene). This type of material combines the elasticity of rubber with the processing convenience of plastic.

[0061] It can be understood that the ethylene-vinyl acetate copolymer or ethylene-acrylate copolymer is any number between 35 and 55 parts, such as 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, etc.; the polyolefin elastomer is any number between 10 and 15 parts, such as 10 parts, 12 parts, 15 parts, etc.; the phosphorus-based flame retardant is any number between 10 and 20 parts, such as 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, etc.; the nitrogen-based flame retardant is any number between 10 and 20 parts, such as 10 parts, 1 The amount of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is any number between 2 parts, 4 parts, 6 parts, 8 parts, etc., between 2 parts and 8 parts; the amount of the compatibilizer is any number between 3 parts, 5 parts, 8 parts, etc., between 3 parts and 8 parts; the amount of the crosslinking agent is any number between 0.5 parts, 1 part, 1.5 parts, 2.0 parts, 2.5 parts, 3.0 parts, etc., between 0.5 parts and 3 parts.

[0062] It can be understood that when R1 connected to Si in the inorganic silicon cage core is a phenylene group, since the phenylene group contains a benzene ring, the carbon-to-hydrogen ratio and the carbon content of the benzene ring are relatively high. When burned, it works together with the large amount of Si contained in the inorganic silicon cage core to further improve the flame retardant properties of the inorganic silicon cage core, thereby improving the flame retardant properties of the modified polyhedral oligomeric silsesquioxane flame retardant synergist.

[0063] It is understandable that phosphorus-based flame retardants decompose to form a non-flammable liquid film of phosphoric acid during combustion. At the same time, phosphoric acid is further dehydrated to form metaphosphoric acid, which is further polymerized to form polymetaphosphoric acid. In this process, not only does the covering layer generated by phosphoric acid have a covering effect, but also because the generated polymetaphosphoric acid is a strong acid and a strong dehydrating agent, it dehydrates the polymer and carbonizes it, changing the mode of the polymer combustion process and forming a carbon film on its surface to isolate the air, thereby exerting a stronger flame retardant effect. At the same time, phosphorus-based flame retardants are also a free radical scavenger. Using mass spectrometry technology, it is found that any phosphorus-containing compound forms PO· when the polymer burns. It can combine with hydrogen atoms in the flame area to suppress the flame. In addition, the moisture produced by phosphorus-based flame retardants during the flame retardant process can, on the one hand, reduce the temperature of the condensed phase, and on the other hand, dilute the concentration of combustibles in the gas phase, thereby better playing a flame retardant role. Nitrogen-based flame retardants decompose at high temperatures to produce non-combustible gases such as ammonia, water vapor, and nitrogen. These gases can dilute the concentration of combustibles in the gas phase and inhibit combustion. The two work synergistically in the condensed phase and gas phase to increase the carbonization rate, form a more stable and uniform carbon layer, and improve the flame retardant effect. B in the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant has a 2Pz empty orbital that can accept lone pairs of electrons and can produce a synergistic effect when coordinated with phosphorus, thereby improving the flame retardant effect. In addition, boron forms boric acid during the combustion process, and boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores are decomposed by heat to form a dense ceramic barrier layer, which isolates the release of combustible gases and the entry of external heat into the interior; the ring structure R2 with a carbon-hydrogen ratio greater than 1 has a higher carbon-hydrogen ratio, and the benzofuran group and polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material.The modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant contains a large amount of silicon and oxygen elements. During the combustion of the polymer, it forms phosphate with the acidic gas after the phosphorus flame retardant is burned, which promotes the reaction between the phosphorus element and the polymer, thereby quickly forming a carbon layer. The SiO2 generated after the combustion of the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant is interspersed in the coke layer, similar to the role of sand in cement, making the coke layer more stable. The coke layer makes it difficult for heat to penetrate the condensed phase, preventing oxygen from entering the combustion area and the gaseous or liquid products generated by degradation from overflowing the surface of the material. The boron of the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant has a 2Pz empty orbital, which can accept lone pairs of electrons and can produce a synergistic effect by coordinating with phosphorus. The synergistic effect of boron and phosphorus makes the above reaction faster. At the same time, the combustion of the nitrogen flame retardant produces a large amount of non-combustible gas, which causes the system in the molten state of the incompletely carbonized part of the cross-linked polyolefin to foam, so that the burning polymer produces a large number of pores. At the same time, the organic matter continues to react, dehydrate and carbonize to form inorganic matter and carbon residue. When the reaction is completed, the system gels and solidifies, and finally forms a porous foam carbon layer.

[0064] The cross-linked polyolefin material of the present invention comprises ethylene-vinyl acetate copolymer or ethylene-acrylate copolymer, polyolefin elastomer, phosphorus flame retardant, nitrogen flame retardant, modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, compatibilizer and cross-linking agent. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives cooperates with the phosphorus flame retardant providing the acid source and the nitrogen flame retardant providing the gas source to synergize and flame retardant, thereby reducing the amount of the flame retardant and improving the flame retardant and mechanical properties of the cross-linked polyolefin material. The cross-linked polyolefin material provided by the present invention has excellent flame retardant properties.

[0065] In some embodiments, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group.

[0066] The carbon-to-hydrogen ratio and carbon content in phenyl are both high, which can slow down the spread of flames during combustion. When the flame is removed, it can quickly extinguish itself, reducing the duration and intensity of combustion. The furan group has a high carbon content and contains oxygen elements that do not participate in combustion. The combination of the two forms a benzofuran group or dibenzofuran group that has both a high carbon-to-hydrogen ratio and a low combustion element. The two work together to form a glass-like protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air and prevent heat transfer, while reducing the content of combustibles and indirectly promoting carbonization.

[0067] In some embodiments, R2 is a benzofuranyl group.

[0068] In some embodiments, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group, and a perylene ring group.

[0069] The naphthalene ring group, anthracene ring group, phenanthrene ring group, acenaphthene ring group, fluorene ring group and perylene ring group have a relatively high carbon-hydrogen ratio and contain a large amount of carbon elements, which makes it easier to form a glass-like protective film or a heat-insulating coke layer when burned.

[0070] In some embodiments, R2 is a naphthyl ring group.

[0071] In some embodiments, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

[0072]

[0073] In some embodiments, the molar ratio of compound 1 to compound 2 during the above reaction is 2:1.

[0074] The spatial structure of compound 1 polyhedral oligomeric silsesquioxane is relatively large. In the reaction, it is necessary to ensure that compound 2 has a sufficiently small spatial steric hindrance so that it can react with compound 1 to obtain compound 3 modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. During the reaction, each compound 2 is connected to two compounds 1, that is, the molar ratio of compound 1 to compound 2 is 2:1, which ensures sufficient space for compound 3 and achieves structural stability of compound 3. Compound 2 contains two hydroxyl groups, and the two hydroxyl groups of one compound 2 are respectively combined with one amino group in two compounds 1 to undergo a dehydration reaction to obtain compound 3. The overall reaction requires a single substance, is simple to operate, and is easy to implement.

[0075] In some embodiments, compound 1 is aminopropyl heptaisobutyl caged polysilsesquioxane.

[0076] In some embodiments, compound 1 is aminophenyl heptaisobutyl caged polysilsesquioxane.

[0077] In some embodiments, compound 2 is benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid.

[0078] In some embodiments, compound 2 is dibenzofuran-3-boronic acid.

[0079] In some embodiments, the structural formula of compound 3 is:

[0080]

[0081] The following is designated as modified POSS flame retardant synergist 1.

[0082] In some embodiments, the structural formula of compound 3 is:

[0083]

[0084] The following is designated as modified POSS flame retardant synergist 2.

[0085] In some embodiments, the preparation method of compound 3 comprises the following steps:

[0086] Compound 1 is dissolved in an organic solvent, and an aqueous solution of compound 2 is added under the action of a catalyst, and the mixture is subjected to a catalytic reaction, and then washed and dried to obtain compound 3;

[0087] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;

[0088] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

[0089] In some embodiments, the catalyst is acetic acid.

[0090] In some embodiments, the solvent is ethanol.

[0091] In some embodiments, the raw material of the cross-linked polyolefin material further includes polyethylene, and the polyethylene accounts for 5-10 parts by weight.

[0092] In some embodiments, the polyethylene includes at least one of low density polyethylene, linear low density polyethylene, medium density polyethylene, high density polyethylene, and metallocene polyethylene.

[0093] It can be appreciated that polyethylene can further improve the tensile strength of the cross-linked polyolefin material.

[0094] In some embodiments, the ethylene-acrylic acid ester copolymer includes at least one of ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, and ethylene-methyl methacrylate copolymer.

[0095] In some embodiments, the polyolefin elastomer includes at least one of ethylene-butene copolymer and ethylene-octene copolymer.

[0096] In some embodiments, the phosphorus-based flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, wherein the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate, phosphite, and phosphorus oxide;

[0097] And / or, the nitrogen-based flame retardant includes at least one of melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, and melamine.

[0098] It is understood that the phosphorus-based flame retardants include, but are not limited to, aluminum hypophosphite, calcium hypophosphite, diethyl aluminum hypophosphite, methylethyl aluminum hypophosphite and phenyl aluminum hypophosphite.

[0099] In some embodiments, the phosphorus-based flame retardant is diethyl aluminum phosphite.

[0100] In some embodiments, the nitrogen-based flame retardant is melamine urate.

[0101] In some embodiments, the cross-linking agent includes, but is not limited to, trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTAMA), triallyl isocyanurate (TAIC).

[0102] In some embodiments, the compatibilizer is a maleic anhydride grafted compatibilizer, including but not limited to PE grafted maleic anhydride (PE-g-MAH), POE grafted maleic anhydride (POE-g-MAH), PP grafted maleic anhydride (PP-g-MAH) and EMA grafted maleic anhydride (EMA-g-MAH). The above compatibilizers enhance the polarity and reactivity of the base material by grafting maleic anhydride (MAH), a polar monomer, onto polyethylene (PE), polyolefin elastomer (POE), polypropylene (PP) and ethylene-maleic anhydride copolymer (EMA), thereby improving their compatibility with other polar materials to improve the performance of the product in all aspects.

[0103] In some embodiments, the raw material of the cross-linked polyolefin material further includes at least one of a lubricant, an antioxidant, and a light stabilizer; wherein, based on the raw materials in parts by weight, the lubricant is 0.2-1 part, the antioxidant is 0.5-2 parts, and the light stabilizer is 0.2-1 part.

[0104] In some embodiments, the lubricant includes but is not limited to PTFE powder, zinc stearate, magnesium stearate, silicone, calcium stearate or ethylene bis stearamide. By adding a lubricant, it is beneficial to promote the mixing of various raw materials to be more uniform, while improving the fluidity of the polymer resin, reducing the friction coefficient, making the surface of the product smoother, improving processing efficiency, and improving the transparency and gloss of the plastic. The type of lubricant is not limited here, and those skilled in the art can select it according to actual needs.

[0105] In some embodiments, the antioxidant includes but is not limited to asymmetric hindered phenol antioxidants, aromatic amine antioxidants, thioether antioxidants, and phosphite antioxidants. Hindered phenol antioxidants include but are not limited to antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), BHT (2,6-di-tert-butyl-p-cresol), antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate); aromatic amine antioxidants include but are not limited to diphenylamine, p-phenylenediamine and dihydroquinoline and its derivatives or polymers, such as antioxidant 445 (4,4'-bis(α.α- The antioxidants include, but are not limited to, dimethylbenzyl)diphenylamine); thioether antioxidants include, but are not limited to, DLTP (dilauryl thiodipropionate), DSTDP (distearate thiodipropionate), and DSTP (octadecyl thiodipropionate); phosphite antioxidants include, but are not limited to, antioxidant 168 (tris[2.4-di-tert-butylphenyl]phosphite), antioxidant 618 (pentaerythritol diphosphite distearyl), and antioxidant 626 (bis[2.4-di-tert-butylphenyl]pentaerythritol diphosphite). By adding antioxidants, the antioxidant properties and aging resistance of polymer materials are beneficial, and the service life of polymer materials is extended. The types of antioxidants are not limited here, and those skilled in the art can choose according to actual needs.

[0106] In some embodiments, the light stabilizer includes but is not limited to light shielding agents, ultraviolet light absorbers, and hindered amine light stabilizers. Light shielding agents include but are not limited to zinc oxide and titanium dioxide; ultraviolet light absorbers include but are not limited to benzophenone, salicylic acid, and benzotriazole; hindered amine light stabilizers include but are not limited to piperidine derivatives, and piperidine derivatives hindered amine light stabilizers include but are not limited to polysuccinic acid (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) ester, benzoic acid (2,2,6,6-tetramethyl-4-hydroxypiperidinyl) ester, and sebacate bis (2,2,6,6-tetramethyl-4-hydroxypiperidinyl) ester.

[0107] In a second aspect of the present invention, there is provided a method for preparing the above cross-linked polyolefin material, comprising the following steps:

[0108] The raw materials, including ethylene-vinyl acetate copolymer or ethylene-butyl acrylate copolymer, polyolefin elastomer, phosphorus flame retardant, nitrogen flame retardant, modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, compatibilizer, and crosslinking agent, are mixed in an internal mixer according to weight parts to obtain an internal mixer material;

[0109] The mixed material is extruded and granulated through an extruder, and dried to obtain a granular material, namely the cross-linked polyolefin material.

[0110] In some embodiments, the raw material further comprises at least one of a lubricant, an antioxidant, and a light stabilizer;

[0111] And / or, the extruder is a twin-screw extruder, the aspect ratio of the twin-screw extruder is (35-40):1, and the extrusion temperature is 110°C-150°C;

[0112] And / or, the drying temperature is 80°C-90°C.

[0113] The content of the present invention is explained below through specific examples and data.

[0114] The information of the raw materials involved in the specific implementation is shown in Table 1:

[0115] Table 1 Information of raw materials of Examples and Comparative Examples

[0116]

[0117]

[0118] Preparation method of modified POSS flame retardant synergist 1

[0119] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 1.

[0120] Preparation method of modified POSS flame retardant synergist 2

[0121] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of dibenzofuran-3-boric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain dibenzofuran-3-boric acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 2.

[0122] Preparation method of modified POSS flame retardant synergist 3

[0123] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of methylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain methylboric acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 3.

[0124] Preparation method of modified POSS flame retardant synergist 4

[0125] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of phenylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain phenylboronic acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 4.

[0126] Embodiment 1:

[0127] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0128] 35 parts of ethylene-vinyl acetate copolymer;

[0129] 15 parts of octacarbon POE;

[0130] 20 parts of diethyl aluminum hypophosphite;

[0131] 20 parts of melamine urate;

[0132] 18 parts of modified POSS flame retardant synergist;

[0133] PE-g-MAH 3 parts;

[0134] 3 parts of TMPTA;

[0135] PE wax 0.5 parts;

[0136] Antioxidant 10100.5 parts;

[0137] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0138] The preparation method is:

[0139] The raw materials, including ethylene-vinyl acetate copolymer, eight-carbon POE, diethyl aluminum hypophosphite, melamine urate, modified POSS flame retardant synergist 1, PE-g-MAH, and TMPTA, are mixed in an internal mixer according to weight parts to obtain an internal mixer material;

[0140] The mixed material is extruded and granulated at 110°C-150°C by a twin-screw extruder with a length-to-diameter ratio of (35-40):1 to obtain a granular material;

[0141] The granules are dried at 80° C.-90° C. to obtain a cross-linked polyolefin material.

[0142] Embodiment 2:

[0143] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0144] 55 parts of ethylene-vinyl acetate copolymer;

[0145] 10 parts of octacarbon POE;

[0146] 10 parts of diethyl aluminum hypophosphite;

[0147] 15 parts of melamine urate;

[0148] 12 parts of modified POSS flame retardant synergist;

[0149] PE-g-MAH 5 parts;

[0150] TMPTA 0.5 parts;

[0151] PE wax 0.5 parts;

[0152] Antioxidant 10100.5 parts;

[0153] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0154] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0155] Embodiment 3:

[0156] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0157] 45 parts of ethylene-vinyl acetate copolymer;

[0158] 12 parts of octacarbon POE;

[0159] 15 parts of diethyl aluminum hypophosphite;

[0160] 15 parts of melamine urate;

[0161] 15 parts of modified POSS flame retardant synergist;

[0162] PE-g-MAH 5 parts;

[0163] TMPTA 1.8 parts;

[0164] PE wax 0.5 parts;

[0165] Antioxidant 10100.5 parts;

[0166] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0167] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0168] Embodiment 4:

[0169] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0170] 35 parts of ethylene-vinyl acetate copolymer;

[0171] 10 parts of octacarbon POE;

[0172] 20 parts of diethyl aluminum hypophosphite;

[0173] 10 parts of melamine urate;

[0174] 18 parts of modified POSS flame retardant synergist;

[0175] PE-g-MAH 8 parts;

[0176] TMPTA 1.8 parts;

[0177] PE wax 0.5 parts;

[0178] Antioxidant 10100.5 parts;

[0179] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0180] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0181] Embodiment 5:

[0182] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0183] 45 parts of ethylene-vinyl acetate copolymer;

[0184] 12 parts of octacarbon POE;

[0185] Metallocene polyethylene 5 parts;

[0186] 15 parts of diethyl aluminum hypophosphite;

[0187] 15 parts of melamine urate;

[0188] 15 parts of modified POSS flame retardant synergist;

[0189] PE-g-MAH 5 parts;

[0190] TMPTA 1.8 parts;

[0191] PE wax 0.5 parts;

[0192] Antioxidant 10100.5 parts;

[0193] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0194] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0195] Embodiment 6:

[0196] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0197] 45 parts of ethylene-vinyl acetate copolymer;

[0198] 12 parts of octacarbon POE;

[0199] 10 parts of metallocene polyethylene;

[0200] 15 parts of diethyl aluminum hypophosphite;

[0201] 15 parts of melamine urate;

[0202] 15 parts of modified POSS flame retardant synergist;

[0203] PE-g-MAH 5 parts;

[0204] TMPTA 1.8 parts;

[0205] PE wax 0.5 parts;

[0206] Antioxidant 10100.5 parts;

[0207] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0208] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0209] Embodiment 7:

[0210] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0211] 45 parts of ethylene-methyl acrylate copolymer;

[0212] 12 parts of octacarbon POE;

[0213] 15 parts of diethyl aluminum hypophosphite;

[0214] 15 parts of melamine urate;

[0215] 15 parts of modified POSS flame retardant synergist;

[0216] PE-g-MAH 5 parts;

[0217] TMPTA 1.8 parts;

[0218] PE wax 0.5 parts;

[0219] Antioxidant 10100.5 parts;

[0220] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0221] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0222] Embodiment 8:

[0223] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0224] 45 parts of ethylene-vinyl acetate copolymer;

[0225] 12 parts of octacarbon POE;

[0226] 15 parts of diethyl aluminum hypophosphite;

[0227] 15 parts of melamine urate;

[0228] 25 parts of modified POSS flame retardant synergist;

[0229] PE-g-MAH 5 parts;

[0230] TMPTA 1.8 parts;

[0231] PE wax 0.5 parts;

[0232] Antioxidant 10100.5 parts;

[0233] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0234] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0235] Embodiment 9:

[0236] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0237] 45 parts of ethylene-vinyl acetate copolymer;

[0238] 12 parts of octacarbon POE;

[0239] 15 parts of diethyl aluminum hypophosphite;

[0240] 15 parts of melamine urate;

[0241] 15 parts of modified POSS flame retardant synergist;

[0242] PE-g-MAH 5 parts;

[0243] TMPTA 1.8 parts;

[0244] PE wax 0.2 parts;

[0245] Antioxidant 10101.2 parts;

[0246] 1 part of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0247] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0248] Embodiment 10:

[0249] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0250] 45 parts of ethylene-vinyl acetate copolymer;

[0251] 12 parts of octacarbon POE;

[0252] 15 parts of diethyl aluminum hypophosphite;

[0253] 15 parts of melamine urate;

[0254] 15 parts of modified POSS flame retardant synergist;

[0255] PE-g-MAH 5 parts;

[0256] TMPTA 1.8 parts;

[0257] 1 part of PE wax;

[0258] Antioxidant 10100.5 parts;

[0259] 0.2 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0260] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0261] Embodiment 11:

[0262] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0263] 45 parts of ethylene-vinyl acetate copolymer;

[0264] 12 parts of octacarbon POE;

[0265] 15 parts of diethyl aluminum hypophosphite;

[0266] 15 parts of melamine urate;

[0267] 15 parts of modified POSS flame retardant synergist;

[0268] PE-g-MAH 5 parts;

[0269] TMPTA 1.8 parts;

[0270] PE wax 0.6 parts;

[0271] 10102 parts of antioxidant;

[0272] 0.6 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0273] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0274] Comparative Example 1:

[0275] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0276] 45 parts of ethylene-vinyl acetate copolymer;

[0277] 12 parts of octacarbon POE;

[0278] 8 parts of diethyl aluminum hypophosphite;

[0279] 15 parts of melamine urate;

[0280] 112 parts of modified POSS flame retardant synergist;

[0281] PE-g-MAH 5 parts;

[0282] TMPTA 1.8 parts;

[0283] PE wax 0.5 parts;

[0284] Antioxidant 10100.5 parts;

[0285] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0286] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0287] Comparative Example 2:

[0288] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0289] 45 parts of ethylene-vinyl acetate copolymer;

[0290] 12 parts of octacarbon POE;

[0291] 20 parts of diethyl aluminum hypophosphite;

[0292] 15 parts of melamine urate;

[0293] PE-g-MAH 5 parts;

[0294] TMPTA 1.8 parts;

[0295] PE wax 0.5 parts;

[0296] Antioxidant 10100.5 parts;

[0297] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0298] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0299] Comparative Example 3:

[0300] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0301] 45 parts of ethylene-vinyl acetate copolymer;

[0302] 12 parts of octacarbon POE;

[0303] 15 parts of melamine urate;

[0304] 120 parts of modified POSS flame retardant synergist;

[0305] PE-g-MAH 5 parts;

[0306] TMPTA 1.8 parts;

[0307] PE wax 0.5 parts;

[0308] Antioxidant 10100.5 parts;

[0309] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0310] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0311] Comparative Example 4:

[0312] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0313] 45 parts of ethylene-vinyl acetate copolymer;

[0314] 12 parts of octacarbon POE;

[0315] 30 parts of diethyl aluminum hypophosphite;

[0316] 15 parts of modified POSS flame retardant synergist;

[0317] PE-g-MAH 5 parts;

[0318] TMPTA 1.8 parts;

[0319] PE wax 0.5 parts;

[0320] Antioxidant 10100.5 parts;

[0321] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0322] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0323] Comparative Example 5:

[0324] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0325] 45 parts of ethylene-vinyl acetate copolymer;

[0326] 12 parts of octacarbon POE;

[0327] 135 parts of modified POSS flame retardant synergist;

[0328] PE-g-MAH 5 parts;

[0329] TMPTA 1.8 parts;

[0330] PE wax 0.5 parts;

[0331] Antioxidant 10100.5 parts;

[0332] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0333] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0334] Comparative Example 6:

[0335] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0336] 45 parts of ethylene-vinyl acetate copolymer;

[0337] 12 parts of octacarbon POE;

[0338] 35 parts of diethyl aluminum hypophosphite;

[0339] PE-g-MAH 5 parts;

[0340] TMPTA 1.8 parts;

[0341] PE wax 0.5 parts;

[0342] Antioxidant 10100.5 parts;

[0343] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0344] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0345] Comparative Example 7:

[0346] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0347] 45 parts of ethylene-vinyl acetate copolymer;

[0348] 12 parts of octacarbon POE;

[0349] 35 parts of melamine urate;

[0350] PE-g-MAH 5 parts;

[0351] TMPTA 1.8 parts;

[0352] PE wax 0.5 parts;

[0353] Antioxidant 10100.5 parts;

[0354] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0355] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0356] Comparative Example 8:

[0357] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0358] 45 parts of ethylene-vinyl acetate copolymer;

[0359] 12 parts of octacarbon POE;

[0360] 15 parts of diethyl aluminum hypophosphite;

[0361] 15 parts of melamine urate;

[0362] 5 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid;

[0363] PE-g-MAH 5 parts;

[0364] TMPTA 1.8 parts;

[0365] PE wax 0.5 parts;

[0366] Antioxidant 10100.5 parts;

[0367] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0368] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0369] Comparative Example 9:

[0370] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0371] 45 parts of ethylene-vinyl acetate copolymer;

[0372] 12 parts of octacarbon POE;

[0373] 15 parts of diethyl aluminum hypophosphite;

[0374] 15 parts of melamine urate;

[0375] 5 parts of aminopropyl heptaisobutyl caged polysilsesquioxane;

[0376] PE-g-MAH 5 parts;

[0377] TMPTA 1.8 parts;

[0378] PE wax 0.5 parts;

[0379] Antioxidant 10100.5 parts;

[0380] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0381] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0382] Comparative Example 10:

[0383] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0384] 45 parts of ethylene-vinyl acetate copolymer;

[0385] 12 parts of octacarbon POE;

[0386] 15 parts of diethyl aluminum hypophosphite;

[0387] 15 parts of melamine urate;

[0388] 1.6 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid;

[0389] 3.4 parts of aminopropyl heptaisobutyl caged polysilsesquioxane;

[0390] PE-g-MAH 5 parts;

[0391] TMPTA 1.8 parts;

[0392] PE wax 0.5 parts;

[0393] Antioxidant 10100.5 parts;

[0394] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0395] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0396] Comparative Example 11:

[0397] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0398] 45 parts of ethylene-vinyl acetate copolymer;

[0399] 12 parts of octacarbon POE;

[0400] 15 parts of diethyl aluminum hypophosphite;

[0401] 15 parts of melamine urate;

[0402] 35 parts of modified POSS flame retardant synergist;

[0403] PE-g-MAH 5 parts;

[0404] TMPTA 1.8 parts;

[0405] PE wax 0.5 parts;

[0406] Antioxidant 10100.5 parts;

[0407] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0408] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0409] Comparative Example 12:

[0410] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0411] 45 parts of ethylene-vinyl acetate copolymer;

[0412] 12 parts of octacarbon POE;

[0413] 15 parts of diethyl aluminum hypophosphite;

[0414] 15 parts of melamine urate;

[0415] 45 parts of modified POSS flame retardant synergist;

[0416] PE-g-MAH 5 parts;

[0417] TMPTA 1.8 parts;

[0418] PE wax 0.5 parts;

[0419] Antioxidant 10100.5 parts;

[0420] 0.5 parts of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate;

[0421] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0422] The cross-linked polyolefin materials obtained in the above embodiments and comparative examples were injection molded or molded, and the injection molded or molded sheets were irradiated with an electron accelerator at an irradiation dose of 12 Mrad, and flame retardant grade, oxygen index, tensile strength, and elongation at break were tested. The test standards are as follows:

[0423] (1) Flame retardant grade

[0424] The test was conducted according to the UL94 standard, with a sample thickness of 3 mm and a test temperature of 23 ± 2 ° C. Three samples were tested using the UL94 vertical combustion test device of Jiangsu Zhengrui Taibang Electronics Co., Ltd., and any dripping was observed.

[0425] (2) Oxygen index

[0426] According to GB / T 2406.2-2009, the sample size is prepared according to the type IV sample. The test is carried out according to method A-top surface ignition method. The oxygen index of three samples is tested using the oxygen index tester device of Fangshang Analytical Instrument Equipment Factory, Jiangning District, Nanjing, and the results are averaged.

[0427] (3) Tensile strength and elongation at break

[0428] The test was conducted in accordance with Article 9 of GB 1040-2008, the test temperature was 23±2℃, and the tensile test used a standard dumbbell-shaped specimen with a tensile speed of 250mm / min. The tensile strength and elongation at break of three specimens were tested using a micro-controlled electronic universal material tensile machine from Dongguan High-speed Railway Testing Co., Ltd., and the results were averaged.

[0429] The test results are shown in Table 3.

[0430] Table 2 Examples of the present invention and comparative examples

[0431]

[0432]

[0433]

[0434]

[0435] Table 3 Performance test table of the embodiments of the present invention and comparative examples

[0436]

[0437] According to Table 3, it can be seen that the radiation cross-linked polyolefin injection molded sheets of Examples 1-11 have good flame retardant properties, and the flame retardant grades all reach V0 level. The V0 level test does not drip, and the oxygen index is >30, which shows that the radiation cross-linked polyolefin material of the present invention has excellent flame retardant properties. It can be seen from Examples 5 and 6 and Example 1 that the tensile strength of the radiation cross-linked polyolefin injection molded sheets can be further improved by adding metallocene polyethylene, and the tensile strength is >11Mpa, which shows that adding polyethylene can improve the mechanical properties of the cross-linked polyolefin material. It can be seen from Example 3 and Comparative Example 1 that the number of modified POSS flame retardant 1 is too high, the flame retardant grade is V1, and the flame retardant grade does not meet the standard; it can be seen from Example 3 and Comparative Example 2 that when modified POSS flame retardant 1 is not added, the flame retardant grade is V2, the flame retardant grade does not meet the standard, the anti-drip performance is poor, and the tensile strength and elongation at break are reduced; it can be seen from Example 3 and Comparative Example 3 that when phosphorus-based flame retardant diethyl aluminum hypophosphite is not added, the oxygen index is reduced; it can be seen from Example 3 and Comparative Example 4 that when nitrogen-based flame retardant melamine urate is not added, the tensile strength and elongation at break are reduced; it can be seen from Example 3 and Comparative Example 5 that only using When modified POSS flame retardant 1 is used as a flame retardant, the flame retardant grade does not meet the standard; it can be seen from Example 3 and Comparative Example 6 that when only the phosphorus-based flame retardant diethyl aluminum hypophosphite is used, the flame retardant grade does not meet the standard, and dripping, tensile strength and elongation at break are reduced; it can be seen from Example 3 and Comparative Example 7 that when only the nitrogen-based flame retardant melamine urate is used, the flame retardant grade does not meet the standard, and dripping, and the oxygen index are low, which shows that the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergists have a synergistic flame retardant effect with the phosphorus-based flame retardant and the nitrogen-based flame retardant, reducing the amount of various flame retardants while improving the flame retardant properties and mechanical properties of the cross-linked polyolefin material.It can be seen from Example 3 and Comparative Example 8 that the modified POSS flame retardant 1 has higher anti-drip, oxygen index and elongation at break than the benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant; it can be seen from Example 3 and Comparative Example 9 that the modified POSS flame retardant 1 has higher flame retardancy, anti-drip, oxygen index and elongation at break than the aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant; it can be seen from Example 3 and Comparative Example 10 that the modified POSS flame retardant 1 has higher anti-drip, oxygen index and elongation at break than the flame retardant mixed with aminopropyl heptaisobutyl caged polysilsesquioxane and benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid. The flame retardant properties of the present invention are shown in Table 1. The flame retardant properties of the present invention are shown in Table 1. The flame retardant properties of the present invention are shown in Table 2. The flame retardant properties of the present invention are shown in Table 3. The flame retardant properties of the present invention are shown in Table 3. The flame retardant properties of the present invention are shown in Table 4.

[0438] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A cross-linked polyolefin material, characterized in that: The raw materials of the cross-linked polyolefin material include, by weight: 35-55 parts of ethylene-vinyl acetate copolymer or ethylene-acrylate copolymer, Polyolefin elastomer 10-15 parts, Phosphorus flame retardant 10-20 parts, 10-20 parts of nitrogen flame retardant, 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, 3-8 parts of compatibilizer, Crosslinking agent 0.5-3 parts, Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is: Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene; R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

2. The cross-linked polyolefin material according to claim 1, characterized in that: The benzofuran group includes at least one of a benzofuran group and a dibenzofuran group; And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.

3. The cross-linked polyolefin material according to claim 1, characterized in that: The modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

4. The cross-linked polyolefin material according to claim 3, characterized in that: The molar ratio of compound 1 to compound 2 is 2:

1.

5. The cross-linked polyolefin material according to claim 3, characterized in that: The preparation method of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps: Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist; Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives; The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

6. The cross-linked polyolefin material according to claim 1, characterized in that: The raw material of the cross-linked polyolefin material also includes polyethylene, and the polyethylene accounts for 5-10 parts by weight.

7. The cross-linked polyolefin material according to claim 6, characterized in that: The polyethylene includes at least one of low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, and metallocene polyethylene.

8. The cross-linked polyolefin material according to claim 1, characterized in that: The ethylene-acrylate copolymer includes at least one of ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, and ethylene-methyl methacrylate copolymer; And / or, the polyolefin elastomer comprises at least one of ethylene-butene copolymer and ethylene-octene copolymer; And / or, the phosphorus-based flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate, phosphite, and phosphorus oxide; And / or, the nitrogen-based flame retardant includes at least one of melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, and melamine.

9. The cross-linked polyolefin material according to claim 1, characterized in that: The raw materials of the cross-linked polyolefin material also include at least one of a lubricant, an antioxidant, and a light stabilizer; wherein, in terms of weight, the lubricant is 0.2-1 part, the antioxidant is 0.5-2 parts, and the light stabilizer is 0.2-1 part.

10. A method for preparing a cross-linked polyolefin material as claimed in claim 1, characterized in that: The following steps are involved: The raw materials, including ethylene-vinyl acetate copolymer or ethylene-butyl acrylate copolymer, polyolefin elastomer, phosphorus flame retardant, nitrogen flame retardant, modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, compatibilizer, and crosslinking agent, are mixed in an internal mixer according to weight parts to obtain an internal mixer material; The mixed material is extruded and granulated through an extruder, and dried to obtain a granular material, namely the cross-linked polyolefin material.

11. The method for preparing a cross-linked polyolefin material according to claim 10, characterized in that: The raw materials also include at least one of a lubricant, an antioxidant, and a light stabilizer; And / or, the extruder is a twin-screw extruder, the aspect ratio of the twin-screw extruder is (35-40):1, and the extrusion temperature is 110°C-150°C; And / or, the drying temperature is 80°C-90°C.